Reproductive patterns result from age‐related sensitivity to resources and reproductive costs in a mammalian carnivore - Geir Rune Rauset; Matthew Low; Jens Persson (Ecology, 2015)
Although the effects of individual age, resource availability, and reproductive costs have been extensively studied to understand the causes of variation in reproductive output, there are almost no studies showing how these factors interact in explaining this variation. To examine this interaction, we used longitudinal demographic data from an 18‐year study of 53 breeding female wolverines ( Gulo gulo ), and corresponding environmental data from their individual home ranges. Females showed a typical age‐related pattern in reproductive output, with an initial increase followed by a senescent decline in later years. This pattern was largely driven by four processes: (1) physiological/behavioral maturation between ages two and three; (2) age‐related differences in the costs of reproduction resulting in an initial increase, and then a declining probability of breeding two years in a row as individuals aged; (3) resource availability (reindeer [ Rangifer tarandus ] carcass abundance; mostly Eurasian lynx [ Lynx lynx ] kills) in the months preceding parturition, which influenced the probability of having cubs, but only for individuals that had successfully bred in the previous year; and (4) resource availability also influenced the cost of reproduction in an age‐dependent manner, as prime age females that had bred in the previous year were more responsive to resource availability than those at other ages. This study demonstrates that by examining how drivers of reproductive variation interact, we can get a much clearer understanding of the mechanisms responsible for age‐related patterns of reproduction. This has implications not only for general ecological theory, but will also allow better predictions of population responses to environmental changes or management based on a population's age‐structure.